2014
DOI: 10.1038/tp.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of estradiol in fear circuitry: implications for sex differences in psychopathology

Abstract: Over the past two decades, substantial knowledge has been attained about the mechanisms underlying the acquisition and subsequent extinction of conditioned fear. Knowledge gained on the biological basis of Pavlovian conditioning has led to the general acceptance that fear extinction may be a useful model in understanding the underlying mechanisms in the pathophysiology of anxiety disorders and may also be a good model for current therapies treating these disorders. Lacking in the current knowledge is how men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 145 publications
4
103
0
2
Order By: Relevance
“…48 Previous studies in humans have suggested activational effects of estrogens on fear conditioning and, in particular, extinction (recall) processes, as shown by differences between free-cycling women and those using hormonal contraceptives as well as differences during menstrual cycle phases. 8 It was thus suggested that current sex hormone status may have a stronger impact than biological sex on fear and extinction processes. Our data stand in contrast to this and support the notion that sex differences may be more dependent on organizational effects 49 as we find strong sex differences on both fear acquisition and retrieval/expression but little evidence for a modulatory role of current sex hormone status.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…48 Previous studies in humans have suggested activational effects of estrogens on fear conditioning and, in particular, extinction (recall) processes, as shown by differences between free-cycling women and those using hormonal contraceptives as well as differences during menstrual cycle phases. 8 It was thus suggested that current sex hormone status may have a stronger impact than biological sex on fear and extinction processes. Our data stand in contrast to this and support the notion that sex differences may be more dependent on organizational effects 49 as we find strong sex differences on both fear acquisition and retrieval/expression but little evidence for a modulatory role of current sex hormone status.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the role of sex differences in humans has often been neglected and studies often included only male participants. 7,8 When including female participants, studies should control for menstrual cycle phase and the use of hormonal contraceptives because both factors have been shown to have an impact on these brain areas. 9 Obviously, this puts a heavy burden on time management and substantially increases the required number of participants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations